H2O2‐induced hydrogen bond water networks enhanced on stimulated Raman scattering. (2nd September 2019) - Wang, Ying; Li, Fabing; Fang, Wenhui; Sun, Chenglin; Men, Zhiwei
Abstract: Forward stimulated Raman scattering in pure water and H2 O2 –H2 O mixture solutions are investigated under different pump laser energies. Three characteristic peaks are observed in mixture solutions due to the enhancement of hydrogen bonds (H‐bonds) structure of water molecules by H2 O2 . Simultaneously, stimulated Raman scattering lines indicate that high‐pressure ice‐phase is formed in mixture solutions, which is attributed to the reduction of the laser breakdown threshold of liquid water by H2 O2, resulting in a strong dynamic high pressure. Abstract : We analyze the forward stimulated Raman scattering spectra of H2 O2 ‐H2 O mixtures under different pump laser energies. Three characteristic peaks are observed in mixture solutions due to the enhancement of H‐bond structure. The high‐pressure ice‐phase is formed in mixture solutions, which is attributed to the reduction of the laser breakdown threshold of liquid water by H2 O2, resulting in a strong dynamic high pressure.